Existence of Solutions of a Nonlocal Elliptic System via Galerkin Method. (15th May 2012) - Cabada, Alberto; Corrêa, Francisco Julio S. A.
Abstract : By means of the Galerkin method and by using a suitable version of the Brouwer fixed-point theorem, we establish the existence of at least one positive solution of a nonlocal elliptic N -dimensional system coupled with Dirichlet boundary conditions.